2013
DOI: 10.1155/2013/604598
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of New Genotypes of Drumstick Tree (Moringa oleiferaLam.) Using Random Amplified Polymorphic DNA Marker

Abstract: The knowledge of genetic diversity of tree crop is very important for breeding and improvement program for the purpose of improving the yield and quality of its produce. Genetic diversity study and analysis of genetic relationship among 20 Moringa oleifera were carried out with the aid of twelve primers from, random amplified polymorphic DNA marker. The seeds of twenty M. oleifera genotypes from various origins were collected and germinated and raised in nursery before transplanting to the field at University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 18 publications
2
12
1
2
Order By: Relevance
“…Similar patterns were observed with a total of 31.69% variation in the first 3 axes and intermixing of genotypes not specific to their geographic origin 21 . Analysis of molecular variance in the entire population set showed a maximum of 98% variance within the population and 2% among the population which is similar to previous studies where 95% variance within population and 3% among population was reported 21,22 . However, a high level of genetic divergence was observed between populations, which is in contrast to the expectations for a woody, perennial, predominantly out-crossed species which maintain variation within population 3,23 .…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Similar patterns were observed with a total of 31.69% variation in the first 3 axes and intermixing of genotypes not specific to their geographic origin 21 . Analysis of molecular variance in the entire population set showed a maximum of 98% variance within the population and 2% among the population which is similar to previous studies where 95% variance within population and 3% among population was reported 21,22 . However, a high level of genetic divergence was observed between populations, which is in contrast to the expectations for a woody, perennial, predominantly out-crossed species which maintain variation within population 3,23 .…”
supporting
confidence: 89%
“…However, a high level of genetic divergence was observed between populations, which is in contrast to the expectations for a woody, perennial, predominantly out-crossed species which maintain variation within population 3,23 . Calculation of F-statistics showed a mean F ST value of 0.025 indicating a negligible amount of genetic differentiation among accessions, with a negative F IS value (-0.30) representing a heterozygote excess or out-breeding of population which could be related to various factors such as genetic drift, gene flow, selection and mating system 22,24 . Distance-based cluster analysis is in accordance with the results obtained using STRUCTURE and PCoA plot, with no clear geographical isolation of the population studied, which is similar to previous reports using RAPD and SSR markers 21,22 .…”
mentioning
confidence: 99%
“…Nevertheless, this finding Rufai et al (2013) that found only 32.7 % from five accessions of MO in Malaysia. Furthermore, following a MVSP analysis of DNA fragment pattern using UPGMA (Sokal & Michener, 1958) the four MO accessions were found having close genetic similarity ranged between 68.8 % and 74.7 % (Fig.…”
Section: Morphological Differences and Genetic Diversitycontrasting
confidence: 68%
“…Nonetheless, the information on MO genetic diversity from this area is scarce and people generally descriminate them mainly based on the morphological differences of leaf petioles color and fragrance exposure that may reflect their genetic variability and adaptation to environmental conditions. Nevertheless, with the advancement of technology, genetic variation of plants can be determined more accurately using DNA-based analysis such as random amplified polymorphic DNA (RAPD) and,hence, it allows the application for plant breeding and selection as has been reported by Rufai et al (2013) in MO for human food and animal fodder.…”
Section: Introductionmentioning
confidence: 99%
“…Muluvi et al (1999) and Ulloa (2005) used ampliûed fragment length polymorphism (AFLPs) to investigate M. oleifera populations present in Kenya, revealing signiûcant differences between regions and populations. Random ampliûed polymorphic DNA (RAPD) were used to investigate cultivated and non-cultivated populations of M. oleifera in Tanzania (Mgendi et al, 2010), different accessions in Nigeria (Abubakar et al, 2011), accessions present in Brazil (Da Silva et al, 2012), commercially grown varieties in India (Saini et al, 2013), and new genotype developed in different countries (Thailand, USA, India and Malaysia, Tanzania, Taiwan) (Rufai et al, 2013). These studies provided evidences of a high level of genetic diversity in natural population compared to the cultivated ones (Leone et al, 2015), concluding that conservation strategies should be adopted (Shahzad et al, 2013).…”
Section: Morphological Characteristics Genetic Diversity and Domestimentioning
confidence: 99%